Deciphering Proteomic Expression in Inflammatory Disorders: A Mass Spectrometry Exploration Comparing Infectious, Noninfectious, and Traumatic Brain Injuries in Human Cerebrospinal Fluid - Philip Dyhrfort; Caroline Lindblad; Anna Widgren; Johan Virhammar; Fredrik Piehl; Jonas Bergquist; Faiez Al Nimer; Elham Rostami (Neurotrauma Reports)
The central nervous system (CNS) evokes a complex inflammatory response to injury. Inflammatory cascades are present in traumatic, infectious, and noninfectious disorders affecting the brain. It contains a mixture of pro- and anti-inflammatory reactions involving well-known proteins, but also numerous proteins less explored in these processes. The aim of this study was to explore the distinct inflammatory response in traumatic brain injury (TBI) compared with other CNS injuries by utilization of mass-spectrometry. In total, 46 patients had their cerebrospinal fluid (CSF) analyzed with the use of mass-spectrometry. Among these, CSF was collected via an external ventricular drain (EVD) from n = 12 patients with acute TBI. The resulting protein findings were then compared with CSF obtained by lumbar puncture from n = 14 patients with noninfectious CNS disorders comprising relapsing–remitting multiple sclerosis, anti-N-methyl-d-aspartate-receptor encephalitis, acute disseminated encephalomyelitis, and n = 13 patients with progressive multifocal leukoencephalopathy, herpes simplex encephalitis, and other types of viral meningitis. We also utilized n = 7 healthy controls (HC). In the comparison between TBI and noninfectious inflammatory CNS disorders, concentrations of 57 proteins significantly differed between the groups. Among them, 20 and 37 proteins were up- and downregulated, respectively. No proteins were uniquely identified in the TBI group. In the comparison of TBI and HC, 55 proteins were significantly different, with 24 and 31 proteins being up- and downregulated, respectively. Four proteins were uniquely identified in the TBI group, (FGG, HBA1, TKT, CA1). In the TBI versus infectious inflammatory CNS disorders, 57 proteins differed significantly between the groups, with 17 and 40 proteins being up- and downregulated, respectively. No proteins were uniquely identified in the TBI group. Due to large discrepancies between the groups compared, the following proteins were selected for further deeper analysis among those being differentially regulated: APOE, CFB, CHGA, CHI3L1, C3, FCGBP, FGA, GSN, IGFBP7, SERPINA3, SOD3, and TTR. We found distinct proteomic profiles in the CSF of TBI patients compared with HC and different disease controls, indicating a specific interplay between inflammatory factors, metabolic response, and cell integrity. In relation to primarily infectious or inflammatory disorders, unique inflammatory pathways seem to be engaged, and could potentially serve as future treatment targets.